2019
DOI: 10.1186/s13014-019-1249-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II radiation dose escalation trial using simultaneous integrated boost technique with elective nodal irradiation and concurrent chemotherapy for unresectable esophageal Cancer

Abstract: BackgroundTo investigate the safety and tolerability of simultaneous integrated boost (SIB) technique concurrent with elective nodal irradiation (ENI) and dual-drug chemotherapy for patients with unresectable esophageal cancer.MethodsIn phase I, the prophylactic PTV received a stable dose of 50.40Gy/1.80Gy/28f while the boost area was planned with 3 consecutive dose levels: the first dose level was 60.76Gy/2.17Gy/28f, and then escalated approximately every 2 Gy. ENI was incorporated in Clinical Target Volume (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…Besides different definitions of LCR, one reason for this difference could be the use of higher SIB doses of 63 Gy. The significance of patient selection is well-reflected in a recent study of Li et al including patients only up to an age of 70 years with Karnofsky indices of at least 70%, resulting in 1-year OS and LCR rates of 76.9% and 78.8% [ 28 ]. Patients in our cohort were older than most cohorts previously published with a median age of 72 years, reflecting the actual clinical challenge in many western countries facing demographic changes towards growing proportions of elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Besides different definitions of LCR, one reason for this difference could be the use of higher SIB doses of 63 Gy. The significance of patient selection is well-reflected in a recent study of Li et al including patients only up to an age of 70 years with Karnofsky indices of at least 70%, resulting in 1-year OS and LCR rates of 76.9% and 78.8% [ 28 ]. Patients in our cohort were older than most cohorts previously published with a median age of 72 years, reflecting the actual clinical challenge in many western countries facing demographic changes towards growing proportions of elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Song et al demonstrated that 60 Gy dCRT with paclitaxel plus cisplatin treatment for selected elderly patients resulted in encouraging survival outcomes (MST, 26.8 months; 2-years OS for stage I–II and III–IV patients, 76.0 and 38.6%, respectively) and tolerable toxicities (highest grade 3/4, leukopenia, 30.5%). In our institutional experience, only 70% of ESCC patients aged ≤ 70 years could complete at least 5 weekly doublet chemotherapy sessions (paclitaxel plus nedaplatin) during dCRT ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…We designed this study due to the following reasons: First, we previously conducted a prospective phase I/II trial investigating the safety and feasibility of simultaneous integrated boost radiotherapy (SIB-RT) with concurrent chemotherapy in patients with unresectable ESCC, and determined that the recommended SIB-RT dose was 59.92 Gy/50.40 Gy in 28 fractions ( 6 ). Second, the fourth-generation oral fluoropyrimidine S-1 yielded a higher tumor response than and was non-inferior to infusional 5-fluorouracil and UFT (a combination of tegafur and uracil) in phase III trials of patients with gastrointestinal cancer ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the distant metastasis rate was low (28.4%), and most distant metastases (72.0%) were combined with local‐regional recurrences. Another radiation dose escalation method, simultaneous integrated boost (SIB), has also been explored; local control of 67.5%‐78.6% was reported . However, local control of ESCC was not improved by SIB, compared with standard dose .…”
Section: Discussionmentioning
confidence: 99%